Bridging the Digital Divide: Artificial Intelligence Adoption Among Lecturers in Kaduna State, Nigeria - Yakubu, Muhammad Auwal; Sain, Zohaib Hassan; Shehu Lawal, Uthman; Musnandar, Aries (Paedagogia: Jurnal Pendidikan, 2025)
This study investigates the awareness, adoption, and impact of Artificial Intelligence (AI) technologies among lecturers in Kaduna State, Nigeria. It addresses three primary research questions: the extent of lecturers' awareness of AI-powered educational tools, the types of AI technologies currently adopted, and the impact of these technologies on academic activities. Utilizing a descriptive survey design, data were collected from a sample of 420 academic staff across four tertiary institutions using a validated instrument based on a modified Likert scale. The study employs one-sample t-tests to evaluate three hypotheses about awareness, adoption, and impact. Findings reveal that lecturers possess moderate awareness of AI applications and are highly familiar with plagiarism detection and content creation tools but need more understanding of intelligent tutoring systems and adaptive learning platforms. Adoption is selective; AI-powered research assistants and content creation tools are widely used, while technologies like Natural Language Processing (NLP) are less common. The study identifies a positive impact of AI on academic activities, enhancing collaboration and resource accessibility while raising ethical concerns. Statistical analyses indicate significant differences in awareness levels, adoption rates, and perceived impacts among lecturers. These findings suggest varied engagement with AI tools across educational settings in Kaduna State. The study concludes that while there is a positive perception of AI's educational impact, improvements in training and infrastructure are necessary to leverage these technologies fully. Recommendations include organizing workshops to increase familiarity with underutilized AI tools, integrating AI training into professional development, and establishing guidelines for ethical AI use in education.